Sociodemographic determinants of youth sports club participation across two generations: the Young Finns Study - Lounassalo, Irinja; Kukko, Tuomas; Suominen, Tuuli; Palomäki, Sanna; Kaseva, Kaisa; Rovio, Suvi; Pahkala, Katja; Hirvensalo, Mirja; Yang, Xiaolin; Lehtimäki, Terho; Raitakari, Olli; Tammelin, Tuija; et al. (Springer Science and Business Media LLC, 2026)
Aim
Sports club participation (SCP) provides opportunities for physical activity, but not all youth have equal opportunities for it. This study examined the prevalence and disparities in SCP among Finnish youth across two generations (1980–1986 and 2018–2020), focusing on sociodemographic factors.
Subject and methods
The study examined the 9–18-year-olds (n = 3439) of the original Young Finns Study population in the 1980s (1980, 1983, and 1986) and their 8–19-year-old offspring (n = 1156) in the 2020s (2018–2020). Self-reported SCP and its correlates (sex, family income, parental educational attainment, urbanity of residential area, and geographical region) across the two generations were studied within four age groups (8–10-/11–13-/14–16-/17–19-year-olds).
Results
Youth SCP was more prevalent in the 2020s than in the 1980s (p < 0.001). In the 1980s, boys had higher SCP rates than girls (p < 0.001), while this sex difference was no longer observed in the 2020s. Family income was directly associated with SCP in 15–18-year-olds in the 1980s and 8–16-year-olds in the 2020s (p < 0.05). SCP several times a week was less common in rural than in urban areas in both generations (p < 0.05).
Conclusion
By the end of the study period, SCP prevalence had risen and sex differences in SCP had narrowed. However, youth from less affluent families or rural areas still showed lower SCP than those from affluent families or urban areas. Efforts are needed to address these disparities.